JATS: A Java Transformation System - Castor, Fernando; Oliveira, Kellen; Souza, Adeline; Santos, Gustavo; Borba, Paulo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2001: Anais do XV Simpósio Brasileiro de Engenharia de Software, 2001)
In this paper we present JATS, a transformation system for the Java programming language. The system has been designed with the goal of making the process of creating and applying transformations as agile as possible. Also, it features a transformation language which has a syntax very similar to that of Java, decreasing the semantic gap between the transformation language and the language being transformed. JATS may be used to specify and apply a wide range of transformations, including refactorings, refinement laws and code generation.